How Does Self-Declared Chronic Pain Compare to Other Definitions? A Prospective Multicenter Study - Raoul Daoust; Jean Paquet; Jeffrey J. Perry; Justin W. Yan; David Williamson; Véronique Castonguay; Gilles Lavigne; Dominique Rouleau; Justine Lessard; Alexis Cournoyer; null OPUM research group (Pain Research and Management)
Trial Registration: ClinicalTrials.gov identifier: NCT03953534